Adolescent Girls in Guatemala: Can an Empowerment Program Change Perceptions of Gender Equity, Aspirations, and Communication? - Vyas, Amita; Low, Hannah; Nagaraj, Nitasha (Journal of Public Health International, 2021)
While Guatemala has made great strides towards gender equality, it remains a country with vast disparities. Gender sensitization and empowerment programs during adolescence when gender attitudes are formed have the potential to diminish gender inequities. The Girl Rising Pilot Program (GR) is a 24-week curriculum designed for adolescent girls living in the Sololá region where 95% of the total population is indigenous and Mayan. The present pilot study evaluated outcomes of the GR Guatemala pilot program. Specifically, the evaluation examined whether there were differences between baseline and follow-up on perceptions of gender equity, aspirations, and communication for adolescent girls who participated in the GR program. A quasi-experimental study design with a one group pre- and post-test was implemented. The pilot evaluation study included all 265 participants at baseline who participated in the GR program. after controlling for significant variables, it was found that the gender equitable attitudes score and communications scale still significantly increased between baseline and follow-up. The results of this evaluation prove that gender sensitization programs play a key role in forming and changing gender attitudes during adolescence, and have the potential to alter their short and long-term attitudes and beliefs.
Keywords: gender attitudes; girls’ empowerment; adolescent girls; adolescent intervention